Early Islam An Arab Christian Perspective - Rāḥib, Mitrī 1962- (2022)
The essay provides an Arab Christian perspective on early Islam. It examines the geopolitical and ecclesial context in which early Islam emerged in the seventh-century Middle East. In a context marked by religious fluidity and national churches, the essay argues that Qur’anic verses form the basis for viewing early Islam as part and parcel of the reception history of the Judeo-Christian tradition of late antiquity.
Keywords: Prophet; Middle Eastern Christianity; Christian-Muslim relations; Qur’anic Studies; Arab Christianity; Early Islam